Aplikasi metode FMEA sebagai Upaya Pengendalian Kecacatan Produksi Kain Weaving, Studi Kasus: PT X - Nugraha, Evan; Mulyani Sari, Rini (Journal of Management and Bussines (JOMB), 2024)
This study aims to identify and analyze the factors causing defects using Failure Mode and Effect Analysis (FMEA) and formulate improvement plans to improve business processes. The research method used is FMEA analysis to find and reduce the factors causing defects. The results of the analysis show that human factors contribute 25%, material factors 26%, and method factors 24% to defects. The conclusion is that FMEA is effective in identifying the main causes of defects and providing a basis for improving the production process. Keywords: FMEA, Quality, Weaving